Managing social networking stress: the role of self-management in reducing social media exhaustion and improving higher education employee performance - Moughal, Wajiha; Nordin, Shahrina Md.; Salleh, Rohani Bt; Abbasi, Haider Ali (Frontiers in Psychology, 2023)
This study investigates the significance of self-management in academic staff stress management related to social networking sites (SNS). It emphasizes particularly on reducing social media exhaustion and increasing job effectiveness. The research applies the stressorstrain-outcome theory and the Smart PLS (Partial Least Squares) analytical approach to examine data from 391 respondents. The study's goal is to provide empirical data on the efficacy of self-control management in reducing SNS stress and its effects on academic staff's psychological well-being and job performance. Data is collected by survey using online email platforms among academic employees, and the collected data is examined utilizing the Smart PLS approach. This approach allows for an investigation of the proposed links and their statistical importance. This research's ramifications are important for academic institutions since its results can help academic personnel effectively cope with SNS-related stress.Academic employees can better limit their SNS usage and avoid social media tiredness by promoting self-control management practices. As a result, academic employees' job performance and overall well-being may increase. The study's findings help to comprehend how self-management might reduce SNS stress and improve staff performance in the academic sector.